1998
DOI: 10.1161/01.cir.98.19.2030
|View full text |Cite
|
Sign up to set email alerts
|

Nonsustained Ventricular Tachycardia in the Setting of Acute Myocardial Infarction

Abstract: Background-Nonsustained ventricular tachycardia (NSVT) has significant prognostic implications in the setting of healing and healed myocardial infarction (MI), but only limited information is available on its importance in the setting of acute MI. We evaluated the prognostic significance of NSVT characteristics in the setting of acute MI. Methods and Results-A prospective database was used to identify 112 patients with NSVT within 72 hours of acute MI.A control group was identified matched for age, sex, type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 28 publications
2
37
0
1
Order By: Relevance
“…Key Words: acute coronary syndrome Ⅲ antiarrhythmic drugs Ⅲ death sudden Ⅲ electrocardiography Ⅲ ventricular tachycardia V entricular ectopy is frequent in patients hospitalized with acute coronary syndromes (ACS). [1][2][3][4] The clinical implications of nonsustained ventricular tachycardia (VT) after ACS remain uncertain, in particular relative to the risk of sudden cardiac death (SCD) in patients with shorter episodes of ventricular ectopy as well as the relationship between the timing of VT after hospital admission and prognosis. Most studies that investigated the incidence of ventricular arrhythmias in the presence of ACS and the relationship with SCD focused on sustained VT and were carried out before widespread use of reperfusion, revascularization, or contemporary medical therapy.…”
Section: Methods and Results-the Metabolic Efficiency With Ranolazinementioning
confidence: 99%
See 1 more Smart Citation
“…Key Words: acute coronary syndrome Ⅲ antiarrhythmic drugs Ⅲ death sudden Ⅲ electrocardiography Ⅲ ventricular tachycardia V entricular ectopy is frequent in patients hospitalized with acute coronary syndromes (ACS). [1][2][3][4] The clinical implications of nonsustained ventricular tachycardia (VT) after ACS remain uncertain, in particular relative to the risk of sudden cardiac death (SCD) in patients with shorter episodes of ventricular ectopy as well as the relationship between the timing of VT after hospital admission and prognosis. Most studies that investigated the incidence of ventricular arrhythmias in the presence of ACS and the relationship with SCD focused on sustained VT and were carried out before widespread use of reperfusion, revascularization, or contemporary medical therapy.…”
Section: Methods and Results-the Metabolic Efficiency With Ranolazinementioning
confidence: 99%
“…Results of a number of studies of acute myocardial infarction, the majority of which focused on STEMI, have shown that ventricular ectopic activity is common (40% to 70%) during hospitalization, with 5% to 10% of patients experiencing an episode of nonsustained VT. [1][2][3][4][5]20 In patients with STEMI, there is conflicting evidence on the relationship between VT and subsequent SCD, with several earlier studies demonstrating an independent relationship between VT and cardiovascular complications 1,5 and subsequent studies failing to find any relation- ship, especially when left ventricular function was considered, 4,21 although these findings have not been uniform. 6,7,22 Relatively little information is available on nonsustained VT in patients with NSTEACS.…”
Section: Ventricular Arrhythmias and Outcomesmentioning
confidence: 99%
“…Such patients have generally been excluded from clinical trials for interventions targeting long-term arrhythmic death risk because of low absolute risk, but it remains unclear whether the magnitude of risk is modulated by the extent of myocardial damage that occurs during the acute event. The long-term risk implications of sustained VT and VF during the acute phase of MI may also be applied to frequent PVCs and runs of NSVT (32). It is important to stress that the clinician's ability to recognize individuals with reversible or transient causes of ventricular tachyarrhythmias is limited (33).…”
Section: Ventricular Tachycardia and Ventricular Fibrillation During mentioning
confidence: 99%
“…Um estudo prospectivo demonstrou que a taquicardia ventricular que se manifesta até as primeiras 12 horas de evolução do quadro isquêmico agudo geralmente não está associada ao pior prognóstico após a alta. Entretanto, os pacientes que evoluem com essa arritmia após as 12 horas têm maior risco de morte súbita, principalmente quando a arritmia se manifesta após as 24 horas de evolução 468 . O tratamento dependerá da manifestação clínica do paciente.…”
Section: -Taquicardia Ventricularunclassified